2014
DOI: 10.1515/ract-2013-2103
|View full text |Cite
|
Sign up to set email alerts
|

Nature of nano-sized plutonium particles in soils at the Hanford Site

Abstract: The occurrence of plutonium dioxide (PuO 2 ) either from direct deposition or from the precipitation of plutonium-bearing solutions in contaminated soils and sediments is well described, particularly for the Hanford site in Washington State. However, past research has suggested that plutonium at the Hanford site may exist in chemical forms in addition to PuO 2 . Although the majority of the plutonium is present as oxide, we present evidence for the formation of nano-sized mixed plutoniumiron phosphate hydroxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 39 publications
2
24
0
Order By: Relevance
“…More recent reports from Felmy et al (2010), Buck et al (2014) and others (Cantrell & Felmy, 2012;Batuk et al, 2015) also used X-ray absorption spectroscopy and TEM to suggest the presence of PuO 2+x particles with P inclusions in these same sediments. A phosphate monohydrate structure possibly containing Fe was even proposed for an observed Pu-P phase investigated in the Z-9 soil using electron diffraction (ED) techniques but was never confirmed (Buck et al, 2014). With this study, we sought to determine if modern SCXRD could help clarify the chemical relationship between Pu and these other elements found in the trench soil.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…More recent reports from Felmy et al (2010), Buck et al (2014) and others (Cantrell & Felmy, 2012;Batuk et al, 2015) also used X-ray absorption spectroscopy and TEM to suggest the presence of PuO 2+x particles with P inclusions in these same sediments. A phosphate monohydrate structure possibly containing Fe was even proposed for an observed Pu-P phase investigated in the Z-9 soil using electron diffraction (ED) techniques but was never confirmed (Buck et al, 2014). With this study, we sought to determine if modern SCXRD could help clarify the chemical relationship between Pu and these other elements found in the trench soil.…”
Section: Introductionmentioning
confidence: 83%
“…Our interest in this area was ignited by a 2015 report in which soil samples taken from the 216-Z-9 radiological waste crib at the Hanford Site in Washington State were stated to possess highly ordered, 10-20 mm Pu-containing particles of a cubic morphology, as determined by micro X-ray fluorescence imaging combined with extended X-ray absorption fine ISSN 1600-5767 # 2019 International Union of Crystallography structure spectroscopy (Batuk et al, 2015). The particles were consistent with a PuO 2+x composition, but evidence for the presence of P and/or Si bonding suggested other species may also be present (Batuk et al, 2015;Buck et al, 2014). In the mid-1970s, larger crystalline PuO 2 particles were characterized and reported from this same radiological waste crib and were determined to contain 70-95% PuO 2 by electron microprobe chemical analysis (Ames, 1974;Price & Ames, 1975;Felmy et al, 2010).…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Phosphate‐based phases play a significant role in the deposition of heavy metals including actinides and especially thorium and uranium . For example, a recent study of contaminated soils and sediments from the Hanford site revealed the presence of nanosized mixed plutonium–iron phosphate minerals that crystallize with the rhabdophane structure . For this reason, actinide and lanthanide phosphate chemistry has benefited from research in the framework of radioactive waste management, especially within the framework of the French research law (the Bataille law) devoted to radioactive waste management.…”
Section: Introductionmentioning
confidence: 99%